Wykorzystanie technologii teleinformatycznych w procesie globalizacji przedsiębiorstw funkcjonujących w Polsce - Moroz, Mirosław (Using information and communication technology in the process of globalization of enterprises located in Poland., 2005)
The paper explores how enterprises located in Poland can benefit from using Information and Communication Technology as a means to face the challenges posed by globalization. In the first place the article examines the notion and role of globalization. Then it has been pointed out that Information and Communication Technology is a way to cope with some problems resulting from globalization. For obvious reasons Information and Communication Technology plays neither main nor single role in the process of globalization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (3); 2005; nr 1093, s. 102-111